Plasmon–Polaron Coupling in Conjugated Polymer on Infrared Nanoantennas - Wang, Zilong (2016)
We propose and demonstrate a novel type of coupling between polarons in a conjugated polymer and localized 11 surface plasmons in infrared (IR) nanoantennas. The near-field interaction between plasmons and polarons is revealed by 12 polarized photoinduced absorption measurements, probing mid-IR polaron transitions, and infrared-active vibrational modes of 13 the polymer, which directly gauge the density of photogenerated charge carriers. This work proves the possibility of tuning the 14 polaronic properties of organic semiconductors with plasmonic nanostructures.